#### Answer

-7

#### Work Step by Step

Write $ F(x)=\frac{f(x)}{g(x)}$, where $ f(x)=x^{9}+x^{8}+4x^{5}-7x $ and $ g(x)=x^{4}-3x^{2}+2x+1$.
Then, $ F'(0)=\frac{f'(0)\cdot g(0)-g'(0)\cdot f(0)}{(g(0))^{2}}=\frac{(-7\cdot1)-(2\cdot 0)}{(1)^{2}}=-7$

Chegg costs money, GradeSaver solutions are free!

Published by
W. H. Freeman

ISBN 10:
1464125260

ISBN 13:
978-1-46412-526-3

-7

You can help us out by revising, improving and updating this answer.

Update this answerAfter you claim an answer you’ll have **24 hours** to send in a draft. An editor
will review the submission and either publish your submission or provide feedback.